Peasant Yard in European North of Russia during Civil War (1917—1921): Characteristics of Survival - V. A. Sablin (Tsentr nauchnykh i obrazovatelnykh proektov, 2021)
The changes in the material well-being of the peasant household in the European North of Russia caused by the agrarian revolution of 1917–1921is examined in the article. The author proceeds from the definition of the European North of Russia as a homo-geneous space, which during the period under study included the Arkhangelsk, Vologda, Severo-Dvinsk provinces, the Karelian Autonomous Soviet Socialist Republic and the Autonomous Region of Komi. The factors that influenced the organizational foundations of peasant production are analyzed. The question is raised about the nature of tax withdrawals from the peasant economy during the Civil War and the transition to a system of in-kind withdrawals and duties. Particular attention is paid to changes in the constituent elements of the peasant budget. The level of needs of a peasant family is shown. The article reveals the dependence of the consumption of the peasant household on the size of the sowing, provision of workers with hands and means of production. Particular attention is paid to the constituent elements of the income and expenditure side of the budget of the peasant parcel. The structure of nutrition of a peasant family in farms of different social types is shown. The characteristics of the survival of the rural courtyard and the main directions of its evolution have been determined. An attempt has been made to compare the material wealth of the peasants and townspeople of the region in the specified period.